2015
DOI: 10.1016/j.rbmo.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Propofol versus thiopental sodium as anaesthetic agents for oocyte retrieval: a randomized controlled trial

Abstract: Clinical outcomes of IVF cycles using propofol or thiopental sodium as anaesthetic agents for oocyte retrieval were compared. The primary outcome measure was fertilization rate per patient. One hundred and eighty patients undergoing ovarian stimulation with gonadotrophins and gonadotrophin-releasing hormone antagonists for IVF were randomized to receive either propofol (n = 90) or thiopental sodium (n = 90). No significant differences in baseline characteristics were present between the two groups. Overall fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, no detrimental effects of propofol on fertilization and the quality of embryos were detected in humans [20]. In the present study, the fertilization rate was similar between the propofol and the control groups, consistent with the previous study [11,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no detrimental effects of propofol on fertilization and the quality of embryos were detected in humans [20]. In the present study, the fertilization rate was similar between the propofol and the control groups, consistent with the previous study [11,21].…”
Section: Discussionsupporting
confidence: 92%
“…Unexpectedly, the number of oocytes retrieved, number of normally fertilized oocytes, number of D3 highquality embryos, and number of frozen embryos in the propofol group were all higher than that in the control group. It seems that propofol used in oocyte retrieval was bene cial and harmless to IVF-ET, while a previous study showed no difference in the embryo quality between patients who received propofol or other anesthesia [21]. However, the limitation of this study is that patients without anesthesia were not included and analyzed.…”
Section: Discussionmentioning
confidence: 88%